Fringe benefits and employee expenses: Tax planning and neutral tax policy* - MACNAUGHTON, ALAN (Contemporary Accounting Research, 1992)
Abstract. This paper constructs a decision model for fringe benefits and employees' work‐related expenses that considers the tax positions of both the employer and the employee. The analytical results obtained can be used to guide tax planning in this area. The decision model is also used to derive tax rules that neither subsidize the provision of fringe benefits nor penalize employees for incurring work‐related expenses. Based on results from the economic theory of rationing, the paper shows that the information required to implement these rules can be obtained from econometric estimates of consumer demand functions. Résumé. L'auteur construit un modèle décisionnel s'appliquant aux avantages sociaux et aux dépenses engagées par les employés dans le cadre de leur travail et quitient compte de la situation fiscale de l'employeur aussi bien que de celle de l'employé. Les résultats analytiques obtenus peuvent servir de guide dans la planification fiscale à cet égard. Le modèle décisionnel est également utilisé pour dériver des règles fiscales qui ne subventionnent pas les avantages sociaux ni ne pénalisent les employés qui engagent des dépenses dans le cadre de leur travail. En s'appuyant sur les résultats de la théorie économique du rationnement, l'auteur démontre que l'information requise pour mettre ces règles en application peut être obtenue à partir d'estimations économétriques des fonctions de demande du consommateur.